PENGEMBANGAN BAHAN AJAR MENGGUNAKAN E-COMIC PADA WEB PIXTON PADA BAB 2 DI BAWAH ATAP - Himmah, Siti Waiqotul; Lina Novita; Fitri Siti Sundari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Siti waiqotul himmah. 037120117. "Development of E-Comic Teaching Materials using Web Pixton on the Topic Under the Roof". This study uses a Research and Development (R&D) approach at Cileungsi 08 public elementary school. The subjects of the study in the trial in developing and determining the feasibility of the designed teaching materials consisted of 28 students. The results showed that the value of the media expert validation was 96%, the language expert validation value was 89%, the material expert validation value was 97% which was included in the "very feasible" criteria. Then the results of the questionnaire on students and showed a value of 93% and teachers 100% with the "very feasible" category. The results of the pre-test and post-test showed an N-Gain of 0.9 in the "high" category, which indicates that this teaching material is very practical or effective. So, overall the results of the development of e-comic teaching materials on the web pixton are very feasible and effective to be used as a learning method.